2019
DOI: 10.1136/bmjopen-2018-026800
|View full text |Cite
|
Sign up to set email alerts
|

The association between the neighbourhood social environment and obesity in Brazil: a cross-sectional analysis of the ELSA-Brasil study

Abstract: ObjectiveTo investigate the association between the neighbourhood social environment, including social cohesion, perceived neighbourhood safety, perceived neighbourhood violence, and obesity in Brazil.DesignCross-sectional study.Setting6 state capitals in Brazil (Salvador, Vitoria, Belo Horizonte, Porto Alegre, Sao Paulo and Rio de Janeiro)ParticipantsCurrent or former employees of five federal universities and one research centre in each of the six Brazilian state capitals who were participants of the baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
2
7
0
1
Order By: Relevance
“…We found that higher education level was associated with lower odds of obesity in women, which is consistent with some studies in the Philippines ( 47 ), Thailand ( 48 ), Tehran ( 49 ), and urban areas such as Zhejiang ( 20 ), Tianjin ( 26 ), Guangdong ( 50 ), and 33 communities of Northeast China ( 51 ). Besides, it was observed in the present study that, men with higher income had higher odds of obesity, which is in agreement with studies in Thailand ( 48 ), Mexican ( 52 ), and other studies in China ( 20 , 51 ), but differs from studies in Molise adults ( 53 ) and Brazil adults ( 54 ). A recent review ( 16 ) concluded that in low-income countries, overweight and obesity are more common in more socioeconomically affluent groups and that this pattern flattens and then reverses as country-level income increases.…”
Section: Discussionsupporting
confidence: 92%
“…We found that higher education level was associated with lower odds of obesity in women, which is consistent with some studies in the Philippines ( 47 ), Thailand ( 48 ), Tehran ( 49 ), and urban areas such as Zhejiang ( 20 ), Tianjin ( 26 ), Guangdong ( 50 ), and 33 communities of Northeast China ( 51 ). Besides, it was observed in the present study that, men with higher income had higher odds of obesity, which is in agreement with studies in Thailand ( 48 ), Mexican ( 52 ), and other studies in China ( 20 , 51 ), but differs from studies in Molise adults ( 53 ) and Brazil adults ( 54 ). A recent review ( 16 ) concluded that in low-income countries, overweight and obesity are more common in more socioeconomically affluent groups and that this pattern flattens and then reverses as country-level income increases.…”
Section: Discussionsupporting
confidence: 92%
“…We found that higher education level was associated with lower odds of obesity in women, which is consistent with some studies in the Philippines (47), Thailand (48), Tehran (49), and urban areas such as Zhejiang (20), Tianjin (26), Guangdong (50), and 33 communities of Northeast China (51). Besides, it was observed in the present study that, men with higher income had higher odds of obesity, which is in agreement with studies in Thailand (48), Mexican (52), and other studies in China (20,51), but differs from studies in Molise adults (53) and Brazil adults (54). A recent review (16) concluded that in low-income countries, overweight and obesity are more common in more socioeconomically affluent groups and that this pattern flattens and then reverses as country-level income increases.…”
Section: Discussionsupporting
confidence: 92%
“… 377 Outro estudo empregando modelos de regressão logística multinível ajustados para idade, educação, cor da pele, estado de residência, nível individual, pontuação de coesão social e violência percebida mostrou que as mulheres que vivem em áreas menos coesas socialmente e bairros considerados mais violentos tiveram maiores chances de obesidade em comparação com suas contrapartes (OR 1,25, IC 95%, 1,02 - 1,53; OR 1,28, IC 95%, 1,04 - 1,56, respectivamente). 378 …”
Section: Obesidade E Sobrepesounclassified